Tradisi Berpakaian Mispa Pasca-Haji dalam Masyarakat Bugis: Studi Kasus Desa Bulu-Bulu, Tonra - Abu Haif; Hasriah Hasanuddin; Muh. Fauzi Isnan; Khaerunnisa Wahid; Firman Natzir; Nur Aidah Fauziah; Nurul Fatimah (Refleksi: Jurnal Kajian Agama dan Filsafat, 2025)
This study examines the tradition of wearing Mispa among the Bugis community in Bulu-Bulu Village, Tonra District, following the performance of the Hajj, from the perspectives of Islamic law and the sociology of religious law. The study aims to explore the social, cultural, and religious foundations underlying the persistence of the Mispa tradition among female pilgrims, as well as to analyze the normative tension between customary practices and Islamic legal prescriptions regarding aurat (modesty requirements). This research employs a qualitative field research method using normative-juridical and empirical approaches, with data collected through observation, in-depth interviews, and documentation. The findings reveal that the tradition of wearing Mispa functions not merely as an item of clothing but as a symbol of honor (siri’), spiritual commitment, and a marker of social identity within Bugis society. The tradition also encompasses socio-economic and cultural dimensions through the involvement of local artisans and constitutes an integral part of post-Hajj cultural expression. However, from the perspective of Islamic law, the practice of wearing Mispa, particularly the use of transparent fabric, raises normative concerns, as it potentially contradicts Islamic prescriptions regarding the covering of aurat. These findings highlight the existence of a dynamic negotiation between customary law and Islamic law, underscoring the importance of cultural and contextual approaches in responding to local religious practices within the demands of Islamic normative frameworks.